Do Corruption and Macoroeconomics Variables Can Influence Foreign Direct Investment ? ( Case Study : Real and USD rate Currency) - Fitri, Suci Alpika; Wardani, Dyah Tities (Universitas Muhammadiyah Yogyakarta, 2021)
Foreign direct investment is a key role importan to encourage economics system for developed and developing countries. foreign direct investment can show dynamic economics and it can build the good relationship with other countries, transfer of technology and knowledge. Higher the level of investment can improve the financial institutuin and economics activities. This study investigates the effect of control of currption on foeign drect investment inflows (FDI) by usingvariables macroeconomics indicators, which include Corruption Perception Index (CPI), Political Stability (POL), Inflation (INF), Exchange Rate (EXR) , Financial Development (FD). This study reveals that the significant factors control of corruption on foreign direct investment in the top 8th muslim countires (Malaysia, Saudi Arabia, UAE, Indonesia, Jordan, Bahrain, and Qatar). Using data from United Naional Conference Trade and Development (UNCTAD) , World Bank and IMF (International Monetary Fund) cover the time period in 2015-2019. This study use the least dummy variales square (LDVS) regression panel data analysis find that effect of corruption on FDI is significantly negative by using real exchange rate currency and the positive effect by using domestic exchange rate (USD). Furthermore, the result of this study give more knowledge of the control of corruption on FDI dynamics in top 8th muslim countries.